2021
DOI: 10.1002/mde.3396
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between corporate social responsibility and earnings management: Sustainable or opportunistic

Abstract: This study examines the association between corporate social responsibility (CSR) and earnings management (EM) among manufacturing firms from a developing economy, Pakistan. To deal with the CSR measurement and data bias, a multimethod approach has applied to measure CSR (both qualitative and quantitative approaches).This research has also established CSR disclosure indices and CSR monetary spending ratio (CSR MSR). Moreover, this research examines both types of EM (accrual-based as well as real activities-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…The Islamic banks may encounter a more critical and wider mismatch between their assets and liabilities which may have a destructive impact on the profitability of banks (Diamond and Rajan, 2005). Several studies (Akhtar, Ali and Sadaqat, 2011;Ramos Meza et al, 2021;Arasu et al, 2021;Shabbir, 2019;Ehsan et al, 2021;Hamza, 2017) found an inverse relationship between liquidity risk and banks performance in the context of Pakistan. Thus, it is hypothesized that an increase in liquidity risk adversely affects both conventional and Islamic banks' performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Islamic banks may encounter a more critical and wider mismatch between their assets and liabilities which may have a destructive impact on the profitability of banks (Diamond and Rajan, 2005). Several studies (Akhtar, Ali and Sadaqat, 2011;Ramos Meza et al, 2021;Arasu et al, 2021;Shabbir, 2019;Ehsan et al, 2021;Hamza, 2017) found an inverse relationship between liquidity risk and banks performance in the context of Pakistan. Thus, it is hypothesized that an increase in liquidity risk adversely affects both conventional and Islamic banks' performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies about loan guarantee in China discussed the motivation of loan guarantees (e.g., Arasu et al, 2021;Beck et al, 2010;Chang & Hong, 2000;Fisman & Wang, 2010;Kumari et al, 2021;Shim, 2006;Uesugi et al, 2010;Wang, 2004), determinants of loan guarantee (e.g., Chen et al, 2011;Feng et al, 2005;Jian & Xu, 2012;Li, 2010;Luo & Tang 2007;Wang & Lin, 2007;) and economic consequences of loan guarantee (e.g. Beck & Demirguc-Kunt, 2006;Chatterjee, 2019;Ehsan et al, 2021;Gao & Song, 2007;Gong & Wu, 2005;Jun et al, 2021;Khanna & Palepu, 2000;Laeven, 2003;Liu et al, 2020;Ma et al, 2014;Matloob et al, 2020;Nguyen et al, 2020;Saleem et al, 2019;Samujh et al, 2012;Shabbir & Wisdom, 2020;Shabbir et al, 2020a,b;Sheng et al, 2016;Uroos et al, 2021;Wang & Luo, 2006;Yu et al, 2020;Wang et al, 2014;Zhang & Jiao, 2017). Hirst et al (2008) suggested that MEF is a critical voluntary disclosure mechanism that can influence a firm's reputation by providing a transparent and accurate report about the firm's credibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following prior research, we assume that CSR may not be the determinant, but the consequence of EM (Choi et al, 2013;Grougiou et al, 2014;MartĆ­nez-Ferrero et al, 2015;Velte, 2019;Faisal et al, 2018;Ehsan et al, 2021). Thus, to address potential reverse Corporate social responsibility causality issues of our topic, we perform a regression analysis on the relationship between EM and CSR and we use the following model:…”
Section: Additional Analysis: Bidirectional Relationshipmentioning
confidence: 99%